Potentials of Thai tropical edible flowers as fresh cut salad mix - S. Sommano (2018)
© 2018 International Society for Horticultural Science. All rights reserved. Antioxidant capacities and total phenolic content of five common Thai edible flowers that have potential as ingredients in salad mix, namely marigold (Tagetes erecta L.), paper flower (Bougainvillea hybrid), ixora (Ixora chinensis Lam.), cape jasmine (Gardenia jasminoides J.Ellis) and damask rose (Rosa damascena Mill.) were investigated. Antioxidant activity by 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging capacity assay and Trolox equivalent antioxidant capacity) (TEAC) and total phenolics content were analysed from the methanolic extract of petals of the flowers. Paper flower, ixora and damask rose gave high DPPH radical scavenging activity (>90% inhibition). All tested flowers had high TEAC (>90% inhibition or 17 mg Trolox g-1sample). Among those flower, damask rose gave highest total phenolic content (31.9 mg GAE g-1sample) followed by marigold and ixora (~28 mg GAE g-1sample). Mixed petals of marigold paper flower, ixora, cape jasmine, and damask rose were packed in polyethylene bags and stored at5 and 13°C. Weight loss and deterioration (%) were evaluated; shelf life of each flower was terminated when >20% of the petals deteriorated. Mixed petals can be kept at low temperatures for 8 and 4 days at 5 and 13°C, respectively. The result from this study could be useful toward marketability and future research opportunity for edible flowers in fresh-cut industry.